Got milk? The effect of export price shocks on exchange rates - Hillary Stein (Federal Reserve Bank of Boston, 2023)
I examine the effect of exogenous terms of trade shocks on an exchange rate by turning to New Zealand's dairy auctions. Dairy is New Zealand's largest export category, making up almost 20 percent of exports. Specifically, whole milk powder accounts for 6 to 11 percent of total exports, and its price is determined in twice-monthly auctions. I use event studies to quantify the impact of surprise auction results on the New Zealand dollar on a high-frequency basis. I find that a 1 percent increase in whole milk powder prices has a modest, but nevertheless significant, effect on the nominal exchange rate that does not seem to be explained by interest rate movements. Rather, the effect seems to be driven by a combination of two channels: a financial flows channel and a fundamental channel. The methodology developed here can potentially be applied to other commodity exporters.
Keywords: F31; F41; G14; 330; exchange rates; commodity prices; terms of trade; event studies